Magnetically steerable gastric capsule endoscopy is equivalent to flexible endoscopy in the detection of markers in an excised porcine stomach model: results of a randomized trial - Hale, Melissa F.; Rahman, Imdadur; Drew, Kaye; Sidhu, Reena; Riley, Stuart A.; Patel, Praful; McAlindon, Mark E. (Endoscopy, 2015)
Background and study aims: Capsule endoscopy is well tolerated but control of its movement is needed in order to visualize the whole gastric surface. Technological developments have produced an external magnet to allow manipulation of the capsule within the gastric cavity. The aim of this study was to compare magnetically steerable gastric capsule endoscopy (MSGCE) with flexible endoscopy for the detection of beads in a porcine stomach.Materials and methods: Beads were sewn onto the mucosal surface of 12 ex vivo porcine stomachs. Each model was examined by flexible endoscopy and MSGCE by two blinded investigators. MSGCE was performed according to a protocol using positional changes and magnetic steering. Outcome measures were number and location of beads identified, and duration of procedure.Results: Flexible endoscopy identified 79 /90 beads (88 %), and MSGCE identified 80 /90 (89 %). The difference in sensitivities was 1.11 (95 % confidence interval 0.06 – 28.26). Thus, MSGCE was noninferior to flexible endoscopy. Mean examination times for flexible endoscopy and MSGCE were 3.34 minutes and 9.90 minutes, respectively.Conclusion: MSGCE was equivalent to conventional flexible endoscopy in the detection of beads in a porcine stomach model.